Tinjauan Yuridis Terhadap Penanaman Modal Asing di Sektor Perikanan Indonesia Setelah Berlakunya Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja - Bernando, Alfredo Joshua (UNES Law Review, 2024)
Indonesia is a maritime country because the lands in Indonesia are surrounded by oceans, so it has the potential that can be developed through the fisheries sector. The fisheries sector can be well developed by investing both foreign and domestic investors. The government has opened the widest possible opportunities for investors since the enactment of Law Number 11 of 2020 concerning Job Creation, so that the fisheries sector in Indonesia can get more attention for foreign investors, because foreign investment can advance the economy in order to realize national development. Therefore, it is hoped that this change in regulations for the fisheries sector can produce maximum results for Indonesia's economic progress through new procedures implemented and supervision by the government itself.